2011
DOI: 10.1186/1556-276x-6-115
|View full text |Cite
|
Sign up to set email alerts
|

Spin effects in InAs self-assembled quantum dots

Abstract: We have studied the polarized resolved photoluminescence in an n-type resonant tunneling diode (RTD) of GaAs/AlGaAs which incorporates a layer of InAs self-assembled quantum dots (QDs) in the center of a GaAs quantum well (QW). We have observed that the QD circular polarization degree depends on applied voltage and light intensity. Our results are explained in terms of the tunneling of minority carriers into the QW, carrier capture by InAs QDs and bias-controlled density of holes in the QW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In Central America, R. prolixus was first reported in 1915 from the city of San Salvador [ 4 ], from where it subsequently spread in El Salvador and into Guatemala, Honduras, Nicaragua, Costa Rica, and southern Mexico. It is believed that the original specimens in San Salvador resulted from a "laboratory accident".…”
Section: Introductionmentioning
confidence: 99%
“…In Central America, R. prolixus was first reported in 1915 from the city of San Salvador [ 4 ], from where it subsequently spread in El Salvador and into Guatemala, Honduras, Nicaragua, Costa Rica, and southern Mexico. It is believed that the original specimens in San Salvador resulted from a "laboratory accident".…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was evidenced the formation of highly spin-polarized two dimensional (2D) 3 gases under high magnetic fields which are responsible for spin polarized injection of carriers into the quantum well (QW) of the RTDs 11 .The formation of excitonic complexes in RTDs at hole and electron resonant tunneling condition was also demonstrated 12,18 . The physical properties of RTDs containing selfassembled InAs quantum dots (QDs) were also investigated [13][14][19][20][21][22] . It was shown that the spin polarization of an ensemble of QDs can also be voltage and light controlled due to the changes of charge state of QDs by an applied voltage, particularly at resonant tunneling condition [13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of RTDs containing selfassembled InAs quantum dots (QDs) were also investigated [13][14][19][20][21][22] . It was shown that the spin polarization of an ensemble of QDs can also be voltage and light controlled due to the changes of charge state of QDs by an applied voltage, particularly at resonant tunneling condition [13][14] . However, there is no study of optical and spin properties of ensemble of InGaAs QRs in RTDs which could be an interesting system to evidence voltage controlled AB effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations